2011
DOI: 10.1177/1934578x1100600122
|View full text |Cite
|
Sign up to set email alerts
|

Composition of a Monoterpenoid-rich Essential Oil from the Rhizome of Zingiber officinale from North Western Himalayas

Abstract: The chemical composition of the essential oil from the rhizome of ginger (Zingiber officinale Roscoe), collected from Nahan, Himachal Pradesh, India, was determined by gas chromatography and GC-MS. Fifty-one compounds, representing 95.1% of the oil, were identified. The oil was characterized by relatively large amounts of the monoterpenoids 1,8-cineole (10.9%), linalool (4.8%), borneol (5.6%), α-terpineol (3.6%), neral (8.1%), geraniol (14.5%), geranial (9.5%), trans-dimethoxy citral (5.0%) and geranyl acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…In another study performed for ginger cultivated in different regions of India, the results varied over a large range from 0.06 to 0.6 mg/kg DM [20]. In ginger cultivated in Ethiopia and Nigeria, the concentration of lead is below the detection level [13,34].…”
Section: Resultsmentioning
confidence: 99%
“…In another study performed for ginger cultivated in different regions of India, the results varied over a large range from 0.06 to 0.6 mg/kg DM [20]. In ginger cultivated in Ethiopia and Nigeria, the concentration of lead is below the detection level [13,34].…”
Section: Resultsmentioning
confidence: 99%
“…Sesquiterpenes are major constituents of the essential oils of turmeric (ar-turmerone, α-turmerone and ß-turmerone) 10 and ginger (zingiberene and ar-curcumene) [34-43], while the monoterpene isomers, neral and geranial, collectively referred to as citral, are only present in GEO and comprise a variable but significant amount by weight (16-75%) [35,37,39-43]. Because estrogenic effects have been reported previously for citral in vitro [17,18], including low affinity estrogen receptor (ER) binding and estrogenic activity, the in vivo effects of GEO were compared to those of 17ß-estradiol in the SCW model.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the study revealed higher percentage of geranial (14.3%) and geraniol (7.3%) [5a]. The study of chemical composition of ginger essential oil from India discovered the large amounts of monoterpenes with lower percentage of 1.8-cineole (10.9%) and higher percentage of geraniol (14.5%) [13]. Another study of ginger essential oil from Ecuador similarly revealed the high percentage of monoterpenes such as citral in contrast to the chemical compound commonly contained in the essential oil of ginger [14].…”
mentioning
confidence: 99%